Development of ranking system for higher education of Ukraine - Zgurovsky, M.; Pankratova, N.; Bobovkin, V.; Linovitskaya, O. (Системні дослідження та інформаційні технології, 2006)
A system of determination of university ranking in Ukraine was developed based on the creation of the corresponding methods adequate to the structure, peculiarities and conditions of the Ukrainian universities functioning. A complex of organizational and program-technical means was proposed for collection of the necessary data and determination of university rankings. For specialists in the field of higher education management, those seeking for higher education and employers. Разработана система определения рейтингов университетов Украины, которая основывается на создании определенной методики, адекватной структуре, особенностям и условиям функционирования отечественной высшей школы. Предложен комплекс организационных и программно-технических средств, который применяется при сборе данных и определении оценок рейтингов университетов для специалистов в области управления высшим образованием, а также желающих получить образование и работодателей. Розроблено систему визначення рейтингів університетів України, яка ґрунтується на створенні відповідної методики, адекватної до структури, особливостей та умов функціонування вітчизняної вищої школи. Запропоновано комплекс організаційних і програмно-технічних засобів, що застосовується при збиранні даних та визначенні оцінок рейтингів університетів для фахівців у галузі управління вищою освітою, а також бажаючих отримати освіту та роботодавців.